The The Influence of Store Atmosphere and Product Quality on Purchasing Decisions with Consumer Satisfaction as an Intervening Variable in Uniqlo Clothing in Semarang City: (Case Study on the Consumer of Uniqlo Products in Semarang City) - Cintya Tri Fitia Fidiana,; Kurniawan, Bayu; Setyorini, Noni (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The purpose of this study is to test and analyze the influence of store atmosphere and product quality on purchasing decisions with consumer satisfaction as an intervening variable. The sample of this study was all customers who had purchased UNIQLO products totaling 384 buyers. Primary data in the study were obtained through questionnaires and measurements using a Likert scale. The research method was through a quantitative approach. The sampling technique in this study used simple random sampling. The data analysis technique used in the study was SEM AMOS. Data processing in this study used the Amos 2.4 tool. Based on the results of the study, it shows that store atmosphere and product quality have an influence on consumer satisfaction. Consumer satisfaction has a significant effect on purchasing decisions. Store atmosphere has no effect on purchasing decisions. Product quality has a significant effect on purchasing decisions. Store atmosphere has a significant effect on purchasing decisions mediated by consumer satisfaction. Consumer satisfaction has a positive effect on purchasing decisions mediated by consumer satisfaction.